2007
DOI: 10.3201/eid/1310.060820
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-ResistantNeisseria meningitidis, Delhi, India

Abstract: Decreased susceptibility of Neisseria meningitidis isolates to ciprofl oxacin emerged from an outbreak in Delhi, India. Results of antimicrobial susceptibility testing of the meningococcal isolates to ciprofl oxacin and further sequencing of DNA gyrase A quinolone-resistance-determining region confi rmed the emergence of ciprofl oxacin resistance in the outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…14 Ciprofloxacin, ceftriaxone, rifampicin, and azithromycin are all effective for chemoprophylaxis, 5,15,16 but ciprofloxacin is the agent of choice because it can be used as a single dose and lacks toxicity. 17 3. Hajj and Umrah meningococcal disease preventative measures: past and current policies and compliance…”
Section: Prevention Of Meningococcal Diseasementioning
confidence: 99%
“…14 Ciprofloxacin, ceftriaxone, rifampicin, and azithromycin are all effective for chemoprophylaxis, 5,15,16 but ciprofloxacin is the agent of choice because it can be used as a single dose and lacks toxicity. 17 3. Hajj and Umrah meningococcal disease preventative measures: past and current policies and compliance…”
Section: Prevention Of Meningococcal Diseasementioning
confidence: 99%
“…Neisseria meningitidis the causative agent of sporadic and epidemic meningitis too has shown resistance to penicillin occasionally (Manchanda et al 2006;Singhal et al 2007).…”
Section: Enteric Pathogensmentioning
confidence: 99%
“…However, all were resistant to cotrimoxazole and two-thirds were non-susceptible to ciprofl oxacin. Singhal et al (2007) have reported ciprofl oxacin-resistant meningococci in an outbreak in Delhi.…”
Section: Drug-resistant Bacteriamentioning
confidence: 99%